2018
DOI: 10.1063/1.5050377
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine arrangements on Ag(100): From pure overlayers of CoPc and F16CuPc to bimolecular heterostructure

Abstract: We have utilized scanning tunneling microscopy (STM) and low energy electron diffraction to determine the structural properties of two types of metal-phthalocyanines (MPcs), i.e., cobalt-phthalocyanine (CoPc) and hexadecafluorinated copper-phthalocyanine (F16CuPc) on the Ag(100) surface. For coverage close to one monolayer, both systems form long-range ordered structures with square unit cells. The size and rotation of the unit cell with respect to the silver lattice depend on the chemical composition of MPc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
2
18
1
Order By: Relevance
“…Formation of perfect chessboard-like superstructures of perfluorinated and nonfluorinated PC molecules was attributed to the directional interaction between partly charged F and H atoms. Following the first observation on highly oriented pyrolytic graphite, , analogous structures have been observed on Ag(111) or Ag(100) …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Formation of perfect chessboard-like superstructures of perfluorinated and nonfluorinated PC molecules was attributed to the directional interaction between partly charged F and H atoms. Following the first observation on highly oriented pyrolytic graphite, , analogous structures have been observed on Ag(111) or Ag(100) …”
Section: Introductionsupporting
confidence: 55%
“…Following the first observation on highly oriented pyrolytic graphite, 29,30 analogous structures have been observed on Ag(111) 31 or Ag(100). 32 In our previous works we studied room-temperature behavior of F 0 CuPC 33 and F 16 CuPC 34 molecules deposited on the Si(111)-Tl 1 × 1 surface. We found that the F 0 CuPC molecules form ordered structures at full ML coverage.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, they are ideal candidates to study the influence of the interaction between the central metal atom and the surrounding ligands on the overall properties. Commonly, metal phthalocyanines and their derivatives have been investigated on crystalline metal surfaces [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. However, the need to electronically decouple organic moieties from the underlying substrates directed the attention towards insulators and/or semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…In the first step of the aforementioned investigations, the procedure for preparation of alternating assemblies of two phthalocyanine molecules was adapted in line with Sabik et al [51][52][53]. We departed from our previously established procedure, where two molecular species, namely MnPc and FeFPc were co-evaporated onto the substrate of choice, kept at room temperature [5,55].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a supramolecular checkerboard structure was described by Yoshimoto et al for a ZnPc and octaethylporphyrin ZnOEP system deposited on Au(111) and Au(100), whereby the study also emphasized the role of the atomic arrangement of the underlying substrate [50]. Moreover, Sabik et al studied CoPc + CuF 16 Pc arrangements on Ag(100) for selected ratios between the two molecular components [51][52][53]. Note that bi-component checkerboards also emerged by the site-specific adsorption of nonfunctionalized porphyrins on a reconstructed Bi on Cu(100) substrate [54].…”
Section: Introductionmentioning
confidence: 84%